Age-Associated DNA Methylation Patterns Are Shared Between the Hippocampus and Peripheral Blood Cells - Harris, Christopher J.; Davis, Brett A.; Zweig, Jonathan A.; Nevonen, Kimberly A.; Quinn, Joseph F.; Carbone, Lucia; Gray, Nora E. (Frontiers in Genetics, 2020)
As the population ages, interest in identifying biomarkers of healthy aging and developing anti-aging interventions has increased. DNA methylation has emerged as a potentially powerful molecular marker of aging. Methylation changes at specific sites in the human genome that have been identified in peripheral blood have been used as robust estimators of chronological age. Similar age-related DNA methylation signatures are also seen in various tissue types in rodents. However, whether these peripheral alterations in methylation status reflect changes that also occur in the central nervous system remains unknown. This study begins to address this issue by identifying age-related methylation patterns in the hippocampus and blood of young and old mice. Reduced-representation bisulfite sequencing (RBSS) was used to identify differentially methylated regions (DMRs) in the blood and hippocampus of 2 and 20 month old C57/Bl6 mice. Of the thousands of DMRs identified genome-wide only 5 were both found in gene promoters and significantly changed in the same direction with age in both tissues. We analyzed the hippocampal expression of these five hypermethylated genes and found that 3 were expressed at significantly lower levels in aged mice (suppressor of fused homolog (Sufu), nitric oxide synthase 1 (Nos1) and tripartite motif containing 2 (Trim2)). We also identified several transcription factor binding motifs common to both hippocampus and blood that were enriched in the DMRs. Overall, our findings suggest that some age-related methylation changes that occur in the brain are also evident in the blood and could have significant translational relevance.